Real-world Evaluation of the Effectiveness of Sinopharm COVID-19 Vaccine Against Symptomatic COVID-19 in an Omicron-Dominant Setting in Mozambique: A Test-Negative, Case-Control Study - Capitine, Igor; Aziz, Asma Binte; Manhiça, Alvaro; Tivane, Inês; Zumba, Absalão; Nhumba, Milton; Rebocho, Zamith; Miquicene, Elias; Nguenha, Neusa; Langa, José; Shrivastava, Harshvardhan; Yang, Yunkai; et al. (Clinical infectious diseases, 2025)
BACKGROUND: We evaluated the effectiveness of the Sinopharm coronavirus disease 2019 (COVID-19) vaccine, introduced in Mozambique, against the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), prevalent from March 2022 to December 2023. - METHODS: A test-negative case-control study was nested in a community-based enhanced COVID-19 surveillance in seven healthcare facilities including mobile testing stations in the Dondo District, Mozambique, between March 2022 and December 2023. Participants were individuals aged ≥2 years with COVID-19-like symptoms for <10 days. Cases were those with polymerase chain reaction (PCR)-confirmed COVID-19. For each case, three PCR test-negative controls were matched, according to age (±5 years), sex, and date of PCR test (±7 days). Follow-up for all cases was conducted until disease resolution. Vaccine protection was assessed according to the association between complete vaccination and SARS-CoV-2 disease onset ≥14 days after vaccination. - RESULTS: The study did not reach the targeted sample size, and only a third were analyzed. A total of 253 cases were matched to 759 test-negative controls by age, sex, and testing date, a process known as matching. Among cases, 41% had one dose of Sinopharm, 53% had two doses, and 6% were unvaccinated. Among the test-negative controls, 37% had 1 dose, 57% had two doses, and 7% were unvaccinated. The adjusted vaccine effectiveness, calculated using matching and adjusted for age and PCR test date, was 18.0% (95% confidence interval, -85.3 to 63.7; P = .63). No COVID-19-positive participants required hospitalization. - CONCLUSIONS: In an Omicron-dominant setting, two doses of the Sinopharm vaccine did not show significant protection against symptomatic COVID-19. However, as our analysis was based on data from only a third of enrolled individuals with confirmed vaccination status, these findings should be interpreted with caution. Our results underscore the importance of real-time vaccine effectiveness evaluations to inform optimal rollout strategies in low- and middle-income countries.